M*A*S*H. Season one [videorecording (DVD)] - Alda, Alan, 1936-; Alda, Alan, 1936-; Rogers, Wayne, 1933-2015; Stevenson, McLean; Swit, Loretta; Linville, Larry, 1939-2000; Burghoff, Gary; Gelbart, Larry; Styler, Burt; Klane, Robert; Marks, Laurence; Dresner, Hal; et al. (M*A*S*H (Television program), 2008)
A television comedy highlighting the outrageous antics of three skilled young surgeons drafted from civilian life and assigned to a unit of the Mobile Army Surgical Hospital (MASH) during the Korean War.